Estética post-humana en la obra gráfica de Claudio Romo - Claire Mercier (Altre Modernità, 2021)
This paper considers the graphic work of the Chilean artist Claudio Romo from a post-human perspective. Romo's work realizes an opening of imaginaries, above all, new configurations of human being, in order to reconsider the boundaries of human nature and propose a new humanism in relation to a new understanding of modernity. After a theoretical tour of post-humanism, especially of Rosi Braidotti's philosophical nomadism, the paper will approach the post-human bestiary that elaborates Romo, on the one hand, as a questioning of access to empirical realities and, on the other hand, as a presentation of potential life forms. The paper will conclude on the presence, in Romo’s work, of a new affirmative humanism, that is, the experimentation of new modes of subjectivization, as well as the approach of new modes of knowledge.